Narcissistic T cells: reactivity to self makes a difference - Paprckova, Darina; Stepanek, Ondrej (The FEBS journal, 2021)
It has been appreciated for more than three decades that the interactions between the T-cell antigen receptor and self-antigens are the major determinants of the cell fates of developing thymocytes and the establishment of central tolerance. However, recent evidence shows that the level of self-reactivity substantially contributes to fate choices of positively selected mature T cells in homeostasis, as well as during immune responses. This implies that individual clones of peripheral T cells are predisposed to specific functional properties based on the self-reactivity of their antigen receptors. Overall, the relative difference in the self-reactivity among peripheral T cells is an important factor contributing to the diversity of T-cell responses to foreign antigens.
Keywords: Autoantigens; self-reactivity; Humans; receptory antigenů T-buněk; Nuclear Receptor Subfamily 4, Group A, Member 1; autoantigeny; T cell; Thymocytes; thymus; lidé; virtual memory; zvířata; Lymphocyte Activation; thymocyty; CD8-Positive T-Lymphocytes; NUR77; tolerance; AIMT; CD8-pozitivní T-lymfocyty; CD5; Receptors, Antigen, T-Cell; aktivace lymfocytů; CD4-Positive T-Lymphocytes; self-antigen; CD4-pozitivní T-lymfocyty; Thymus Gland; Animals; TCR; jaderné receptory - podrodina 4, skupina A, člen 1